Proteomic screening of TMEM43 binding partners identifies VDAC leading to mitochondrial dysfunction - Qingqing Zhu; Guoxing Zheng; Yingsi Lu; Yizhou Jiang; Yan Li; Hong Chen; Lifen Huang; Nannan Tang; Bo Li; Yi Lu; Jian Zhang; Chengming Zhu (PLoS ONE, 2025)
The transmembrane protein 43 (TMEM43) S358L mutation is the most common mutation found in patients with ARVC5, a severe subtype of arrhythmogenic right ventricular cardiomyopathy (ARVC). Characterizing the interacting proteins of TMEM43 mutants is important for unraveling the underlying mechanisms of the relative pathogenesis. Here, we applied quantitative immunoprecipitation (IP)-mass spectrometry (MS) to screen the differential binding partners between TMEM43 and TMEM43 p.S358L and identified 166 interacting protein candidates. Functional enrichment of these proteins highlighted their involvements of calcium signaling, lipid metabolism and cardiovascular diseases. Immunofluorescence (IF) staining and TurboID proximity-labeling further confirmed the interaction of several selected proteins. Moreover, we found that the interaction of both voltage-dependent anion-selective channel proteins (VDAC1 and VDAC2) to TMEM43 mutant significantly decreased. Importantly, lower VDAC binding mediated the mitochondrial dysfunction in cardiac myoblast H9c2 cells of TMEM43 p.S358L. The study provides a comprehensive view of the binding protein landscape of TMEM43 p.S358L, and implies a critical role of TMEM43 in mitochondria.